Equality in Education 2014
DOI: 10.1007/978-94-6209-692-9_14
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Language Anxiety in Relation to Gender Equity in Foreign Language Learning

Abstract: Elis'F' l'lrlllp Wlnrl l(orrrrg (harr llll,ash l ltttvaully Nrllhwt us {l*lrsltn ttnl Christof)lt(,r lkryltr (l rlr,) llntvdntly rtl Naw I nghtnl AntilttilL. Auiltxll, I Etulity itt I du utiutt: luhnerr rrrd llr llllffi lf I llrt. book rr,rrrlrrrlr ur, {lovpnlntcttlt tttm rnJ-i tharrrlr,lvor wlth pollty to nrark ttrtr pitiil inE rlubbrlrrr loor lh,rl arr,provlrrt; lu hs'urmrwhll l)ronoun((,nrcrrls. ilrc r-h,lrr1r, llrrrl llu0o ttln tilh-F-*lt']:,,.Ilmld, actiorl': , t!,:, r'rilrnir r,.r. riiiiidil E irrsightfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…MacIntyre, Baker, Clément, and Donovan (2002), for example, reported that male 7th to 9th grade students in a junior high school enrolled in a French immersion program have maintained the same levels of anxiety, while their female counterparts witnessed a decrease in anxiety levels from 8th to 9th grade. In a more recent study involving 64 Indonesian learners of English in Indonesia and Australia, Hasan and Fatimah (2014) reported that male students exhibited more anxiety than their female peers. These results contradict the findings reported by other studies which found that females tended to suffer from higher levels of FLA (e.g., Arnaiz & Guillén, 2012;Donovan & Maclntyre, 2005;Elkhafaifi, 2005;Machida, 2001;Park & French, 2013).…”
Section: Fla and Gendermentioning
confidence: 97%
“…MacIntyre, Baker, Clément, and Donovan (2002), for example, reported that male 7th to 9th grade students in a junior high school enrolled in a French immersion program have maintained the same levels of anxiety, while their female counterparts witnessed a decrease in anxiety levels from 8th to 9th grade. In a more recent study involving 64 Indonesian learners of English in Indonesia and Australia, Hasan and Fatimah (2014) reported that male students exhibited more anxiety than their female peers. These results contradict the findings reported by other studies which found that females tended to suffer from higher levels of FLA (e.g., Arnaiz & Guillén, 2012;Donovan & Maclntyre, 2005;Elkhafaifi, 2005;Machida, 2001;Park & French, 2013).…”
Section: Fla and Gendermentioning
confidence: 97%
“…Fear of negative evaluation has a broader scope than that of test anxiety as it occurs in a social, evaluative situation, including apprehension, avoidance, and/or expectations of others' negative evaluation. After defining these three factors, Horwitz et al (1986) proposed the FLCAS, which is a 33-item five-point Likert Scale that has been most cited to measure the variable of foreign language anxiety and well-validated by many follow-up studies mainly through factor analysis (e.g., Liu and Huang, 2011;Hasan and Fatimah, 2014;Tsai and Lee, 2018). In addition to the above three-factor solution, follow-up studies using the FLCAS to conduct factor analysis do not have a confirmed classification.…”
Section: Foreign Language Anxietymentioning
confidence: 99%
“…Meanwhile, Dewaele's (2017) study of 1287 female and 449 male students revealed that females had more fun and anxiety in the foreign language class. MacIntyre et al (2002) and Hasan and Fatimah (2014) found that male students experienced greater anxiety than their female counterparts when speaking English. By contrast, Hwa's (2014) exploration of 237 Malaysian undergraduate students showed that female students were significantly more anxious than their male peers when speaking English.…”
Section: Literature Reviewmentioning
confidence: 99%